A Pragmatic Study of Sarcasm in Selected British TV Talk Shows - Asst. Inst. Raneen Waleed Khalid (Periodica Journal, 2022)
An interlocutor may deliver the facts tastefully and softly by applying comedy. This research is an effort to cope with the caustic comments on the British talk shows. The present research tries to find out how '' sarcasm is reflected and expressed in the British talk show; displaying the pragmatic devices of humour and discovering similar tactics. It , furthermore, hypotheses the following; talk show extensively depends on tactics of humour to express the sarcastic message; the strategies are : irony, exaggeration, and sarcasm. This study is relevant to students of linguistics and researchers in the area of pragmatics notably in the theories of sarcasm and humour. This article is devoted to the examination of the British talk programmes
Keywords: Pragmatics; Sarcasm; Talk Shows